Yeast Growth Influenced by Parallel Combination of Time-Varying and Static LF EMF - Roman Radil; Ladislav Janousek (Communications - Scientific letters of the University of Zilina, 2013)
Presented article deals with the mechanisms of low frequency electromagnetic field impact on biological structures. Special attention is paid to the theories describing the influence of applied electromagnetic field on microtubule structures and ions bound on the cell membrane surface. These theories are confronted with the experiments presented herein. For better reliability of the experiments, new exposure coil system has been designed and created. Using this exposure system, results are conducted on the eukaryotic cells represented by saccharomyces cerevisiae. Observed effects show a good correlation mainly with ion parametric resonance model predictions proposed by Lednev and are discussed in the scope of further investigation possibilities.